G449(P) The use of virtual reality headsets as a distraction technique in a paediatric emergency department. (May 2019) - Knight, K; Singh, B; McClenaghan, C
Abstract : Aims: To assess the use of a Virtual reality (VR) head set as a distraction technique in children undergoing short painful procedures (cannulation, venepuncture, wound closure or foreign body removal) in the paediatric Emergency Department. Methods: We compared how distracted children were with VR (Pico Goblin headset, using the 'Happy Place' animated interactive 360 degree experience), with an equivalent group of children with traditional distraction (TD) methods (a play specialist and the child's choice of book, game or tablet computer). Children aged 5 and above were recruited. We excluded children with head, neck or facial injury, history of epilepsy, and nausea or vomiting on presentation. Twenty patients were recruited to each group. Staff rated how distracted the child had been during the procedure using the Children's Emotional Manifestation Scale (CEMS) and rated their pain behaviours using the Face Legs Arms Cry Consolability (FLACC) Scale. Parents also completed a questionnaire on their experience. Results: Patients using VR were more distracted compared those receiving TD (average CEMS score=5 with VR, 6 with TD) but this was not statistically significant (p=0.74). Patients using VR showed fewer reactive pain behaviours than the TD group (FLACC score 0 vs 1.5; p=0.004). Written feedback from parents regarding VR was positive, and staff were enthusiastic about the success of the new technology for distraction. Conclusion: Thirty percent of VR headset use in our department occurred out of hours. A VR headset may provide emergency department staff with a convenient way to offer procedural distraction to children out of hours if there is no play specialist available. We would strongly advocate that a VR headset is not a substitute for the skills and experience of a play specialist who can provide individualised distraction to children, regardless of age, presenting complaint or past medical history. A VR headset is a novel tool that can add to the variety of distraction methods available to play specialists in the Paediatric Emergency Department, but its use should be judged on a case by case basis.